The Impact of Phonology-Based Vocabulary Learning on English Language Skills in the Digital Era - DamayantI, Yulia; Hasbullah, Hasbullah; Sarwadi, Sarwadi (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study investigates the impact of phonology-based vocabulary learning on the English language skills of eighth-grade students at SMP Islam Nurul Qur’an in the academic year 2025/2026. Employing a pre-experimental design with a one-group pre-test and post-test structure, the research involved 20 students from class VIII A as participants. Data collection was conducted through vocabulary tests (pre-test and post-test) and student questionnaires. Statistical analysis was performed using a paired sample t-test in SPSS version 25. The findings revealed a significant improvement in students’ English skills after the implementation of phonology-based learning. The mean pre-test score of 42.00 increased to 68.25 in the post-test, with the t-test showing a significance value of 0.000 (< 0.05). These results indicate that phonology-based vocabulary learning positively influences students’ vocabulary mastery and pronunciation accuracy. Questionnaire data further confirmed students’ positive perceptions, with an average score of 74.10, suggesting that the method enhanced motivation and learning engagement. The study concludes that integrating phonology-based strategies with digital media provides an effective approach to improving English language skills among junior high school students in the digital era.